Microfinance as a livelihood strategy: A case study of forced migrants in Johannesburg - Kamugi, Watetu (My University, 2014)
Microfinance as a tool for development has been used all over the world in combating poverty and improving livelihoods. It is described as the provision of savings, credit and insurance services to low income earners and the very poor in society through Microfinance Institutions (MFI). Additionally, MFI provide vocational training in various skills such as hand crafts, business and language skills. Livelihoods on the other hand constitute the ways in which people access and mobilise resources that enable them to increase their economic security thus reducing the vulnerability created and exacerbated by conflict, and how these resources help them pursue goals necessary for their survival. As a livelihoods strategy for refugees, the services of MFI have mainly been employed in camp settings, with few projects run for urban refugees. Many reasons arise for the difficulty in employing it as a livelihood strategy in urban settings, with the most common being the fluidity and mobility of urban refugees that renders them a risky group to lend money, grants or training to. This study explores the accessibility of microfinance to forced migrants and refugees living in the economic hub of Africa, Johannesburg. The findings suggest that refugees and other forced migrants receiving microfinance heard about the MFI in this particular study- Jesuit Refugee Services (JRS), from their social networks of family and friends while those who had never heard about JRS or any other organization offering microfinance services were in completely different social networks and were of different nationalities from the beneficiaries. As such, the question of accessibility to microfinance is linked to availability of information through social networks. Language also proved to influence the livelihood strategies adapted by the different refugees. Refugees who could speak English and other South African languages were in employment or in trade ventures as they could communicate with host nationals. This is unlike those refugees who only spoke French and Lingala, languages not spoken by South Africans. As such, they needed language training so as to enable them to communicate. The study also found that the main problems faced by refugees in Johannesburg are lack of employment, problems with accommodation, difficulty in enrolling children in public schools and raising the required school fees and difficulties in accessing social services. The research report concludes by recommending solutions to MFI and other organizations whose mandate is to assist refugees and other forced migrants to embrace all vulnerable refugees within the MFI in an effort to make MFI available to all who require their services.